Eruptive-volcanic-basalt structures in the Truong Sa-Spratly Islands and adjacent areas from interpreting gravity and magnetic data - Dung*, Tran Tuan; Minh, Nguyen Quang (Vietnam Journal of Earth Sciences, 2017)
In the Spratly Islands (Truong Sa Islands) and adjacent areas, volcanic activities are quite strong after the sea-floor spreading in the Cenozoic Era. However, it is difficult to define their ranges and spatial locations. Based on the different characteristic between eruptive volcanic basalt and sedimentary rocks near the surface, it can be said that, the blocks which are higher density and magnetization than those surroundings could be identified as eruptive volcanic basalt. This paper presents the methods of reduction to the magnetic equator in low latitudes to bring out a better correlation between magnetic anomalies and their causing-sources; High-frequency filtering is to separate gravity and magnetic anomalies as well as information about the volcanic basalts in the upper part of the Earth’s crust; 3D total gradient is to define the spatial location of high density and magnetic bodies. The potential structures of eruptive volcanic basalt are predictively determined by multi-dimensional correlation analysis between high-frequency gravity and magnetic anomalies with weighted total gradient 3D. The results from the above-mentioned methods have shown that the distribution of the eruptive volcanic basalt mainly concentrates along the Spratly Island’s seafloor-spreading axis, transitional crust, Manila trench and some large fault zones. These results are improved by available seismic data in the study area. References Baranov, V., 1957. A new method for interpretation of aeromagnetic maps: Pseudo-gravimetric anomalies: Geophysics, 22, 359-383. Bhattacharyya, B. K., 1966. Continuous spectrum of the total magnetic field anomaly due to a rectangular prismatic body. Geophysics, 31, 197-212. Bracewell, R., 1999. The Fourier transform and its applications (3nd edition): McGraw-Hill. 496p. Bui Cong Que, Tran Tuan Dung, 2008. Study of crustal structure and Geodynamics in the East Vietnam Sea and adjacent areas. Vietnam Journal of Earth Sciences, 30(4), 481-490. Dang Van Bat, Do Dinh Tat, Mai Thanh Tan, 1994. Characteristics of lithology and fossils of the Oligocene eruption. Vietnam Journal of Earth Sciences, 16(2), 59- 66. Hanoi. Flower M.F.J., Zhang M., Chen C-Y., Tu K., Xie G., 1992. Magmatism in the South China Basin, 2. Post-spreading Quaternary basalts from Hainan Island, south China. Chem. Geol., 97, 65-87. Ian N. MacLeod, Keith Jones, Ting Fan Dai, 1993. 3-D Analytic Signal in the Interpretation of Total Magnetic Field Data at Low Magnetic Latitudes. Exploration Geophysics, 24, 679-688. Karoly I. K, 1990. Transfer properties of the reduction of magnetic anomalies to the pole and to the equator. Geophysics. 55(9), 1141-1147. Le Huy Minh, Luu Viet Hung, Vo Thanh Son, 2003. Reduction to the pole at low latitude and interpretation of the magnetic anomaly map of Vietnam. Vietnam Journal of Earth Sciences, 24(2), 164-174. Lee T-Y., Lo C-H., Chung S-L., Chen C-Y., Wang P-L., Lin W-P., Hoang N., Cung T.C., Nguyen T.Y., 1998. 40Ar/39Ar dating result of Neogene basalts in Vietnam and its tectonic implication. In: M.F.J. Flower et al (Eds.). Mantle Dynamics and Plate Interactions in East Asia. Geodynamics Ser., 27, 317-330. Amer. Geol. Union. Leu, L.-K., 1981. Use of reduction-to-equator process for magnetic data interpretation: Presented at the 51st Ann. Internat. Mtg., Sot. Exnl. Geonhv.: Geophysics, 47. Li S-L., Meng X-H., Guo L-H., Yao C-L., Chen Z-X., Li H-Q., 2011. Gravity and magnetic anomalies field characteristics of the East Vietnam Sea and its application for interpretation of igneous rocks, Applied geophysics, 7(4), 295-305. Li Y., D. W. Oldenburg, 2001. Stable reduction to the pole at the magnetic equator, Geophysics, 66, 571-578. MacLeod, I.N., K. Jones and T.F. Dai, 1993. 3-D analytic signal in the interpretation of total magnetic field data at low magnetic latitudes. Exploration Geophysics, 24(4), 679-688. McElhinny, M.W., 1973. Palaeomagnetism and Plate Tectonics, Cambridge, London, 356pp. Chapter 1 presents an introduction to the geomagnetic field. Nabighian MN, 1984. Toward a three-dimensional automatic interpretation of potential field data via generalized Hilbert transforms: Fundamental relations. Geophysics, 49, 780-786. Nguyen Hoang, Phan Trong Trinh, 2009. Characteristics of lithological and geochemical of Neogene - Quaternary volcanic rocks and mantle dynamics in the East Vietnam Sea and adjacent. Journal of Geology, 312. Pham Tich Xuan, Nguyen Trong Yem, 1999. Volcanic activities in late Cenozoic in Vietnam. Vietnam Journal of Earth Sciences, 12(2), 128-135. Phillips, J. D., 1997. Potential-Field Geophysical Software for the PC, version 2.2: USGS open-File Report , 97-725. Roest, W.R., J. Verhoef and M. Pilkington, 1992. Magnetic interpretation using the 3-D analytic signal: Geophysics, 57(1), 116-125. Sandwell, D. T., Garcia E., Soofi K., Wessel P., and Smith W. H. F, 2013. Towards 1 mGal Global Marine Gravity from CryoSat-2, Envisat, and Jason-1, The Leading Edge, 32(8), 892-899. doi: 10.1190/tle32080892.1. Spector A and Grant FS, 1970. Statistical models for interpreting Aeromagnetic data. Geophys, 35(2), 293-302. Sudhir Jain, 1988. Total magnetic field reduction - The pole or equator? A model study, Canadian journal of exploration in geophysics, 24(2), 185-192. Tran Tuan Dung, 2013. Characteristics of the structure - tectonic in the deep water of the East Sea of Vietnam based on interpretation of gravity and magnetic anomaly data. The 35th Conference of Vietnam Petroleum Institute, 55-66. Tran Tuan Dung, Bui Cong Que, Nguyen Hong Phuong, 2013. The Cenozoic basement structure of the Spratly Islands and adjacent areas by modeling and interpreting gravity data. Russian Journal of Pacific Geology. ISSN 1819-7140, 4, 227-236. http://geomag.org/models/emag2.html. http://www.ngdc.noaa.gov/geomag-web/#declination.